ENT 530 Case Study / Nurul Haidah Saharrudin ... [et al.] - Saharrudin, Nurul Haidah; Saahal, Hanisah; Rowin, Clement; Mohd Farizan, Muhammad Hilman; Manan, Misshirley (2018)
Axia Solution Company have 3 is food and beverages establishment that offered varieties of food and beverages services. Encik Taufiq managed to open three chain food premise which is in Shah Alam, Klang and Puncak Alam area. Among of the places, we choose Puncak Alam area as our investigation research, whereby this premises are operated in cafeteria at Dahlia College.